2020
DOI: 10.1108/cms-05-2019-0167
|View full text |Cite
|
Sign up to set email alerts
|

Thwarted enthusiasm: effects of workplace incivility on newcomer proactive behaviors

Abstract: Purpose The purpose of this study is to explore the relationship between supervisor and coworkers’ workplace incivility and newcomer proactive behaviors. Drawing on conservation of resources (COR) theory, the authors examined resource depletion as a mediator and newcomer proactive personality, as well as their current organizational tenure as moderators of the relationship between workplace incivility toward newcomers and their proactive behaviors. Design/methodology/approach A time-lagged research design wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 81 publications
(100 reference statements)
0
24
0
Order By: Relevance
“…Second, the processes through which workplace incivility affects work outcomes have not previously been adequately studied (Schilpzand et al, 2016), especially the relationship between workplace incivility and proactive work behaviors (Lan et al, 2020; Liu et al, 2019; Schilpzand & Huang, 2018). The current study suggests that the depletion of personal emotional resources mediates the relationship between workplace incivility and personal initiative, which offers a better understanding of the mechanism driving the connections between workplace incivility and proactive performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the processes through which workplace incivility affects work outcomes have not previously been adequately studied (Schilpzand et al, 2016), especially the relationship between workplace incivility and proactive work behaviors (Lan et al, 2020; Liu et al, 2019; Schilpzand & Huang, 2018). The current study suggests that the depletion of personal emotional resources mediates the relationship between workplace incivility and personal initiative, which offers a better understanding of the mechanism driving the connections between workplace incivility and proactive performance.…”
Section: Discussionmentioning
confidence: 99%
“…First, our study extends previous studies on workplace incivility and personal initiative. Previous research has devoted attention to the effect of workplace incivility on negative work outcomes and in-role performance (Cortina et al, 2001;Lim et al, 2008;Pearson et al, 2000Pearson et al, , 2001Penney & Spector, 2005;Sliter et al, 2012;Taylor et al, 2017), while few studies have focused on the effect of workplace incivility on proactive work behaviors (Lan et al, 2020;Liu et al, 2019;Schilpzand & Huang, 2018), such as personal initiative. By examining the link between workplace incivility and personal initiative, our study supplements existing literature on the effect of uncivilized work behaviors on positive work outcomes and enriches the potential antecedents of personal initiative.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we were keen to extend this study’s scope by drawing the samples from all financial services sector organizations, only four organizations in the southern region of Pakistan (based on the lead author’s personal contacts) gave permission for data collection, informally. Following Lan et al (2020) approach, a small group of employees from the selected organizations was first interviewed to determine the extent to which they had been subjected to SI. However, the interviews indicated that SI was high in two of the organizations.…”
Section: Methodsmentioning
confidence: 99%
“…In organizational management research, scholars have proven that distributed leadership has positive impacts on individuals, teams, and organizations (e.g., it promotes employees' taking charge behavior, team performance, and organizational change; Wang et al, 2014;Butler and Tregaskis, 2018;Canterino et al, 2020). Despite these encouraging findings (Crant, 2000;Den Hartog and Belschak, 2012;Lan et al, 2020;Bohlmann and Zacher, 2021), a notable omission is the proactive behavior of new generation employees. Therefore, the first goal of this research is to explore how distributed leadership can effectively promote the proactive behavior of new generation employees.…”
Section: Introductionmentioning
confidence: 99%